If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + x = -1 Solving -15 + x = -1 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + x = -1 + 15 Combine like terms: -15 + 15 = 0 0 + x = -1 + 15 x = -1 + 15 Combine like terms: -1 + 15 = 14 x = 14 Simplifying x = 14
| (4x^5-3x^4)/(5x^2) | | 18/13/13 | | 2/3x+1/10=-1/3x-1/3 | | 34a=272 | | -19n=-57 | | 5x-3-9+6=45 | | -71/144-5/12 | | 0=4t-16t^2 | | 8(x+3.14)+3.14(112+x)=180 | | 204=57x | | 1/125+2/15 | | 3x+5x-35=17 | | 22d/17 | | m-2/24=-1 | | 7x+32=10 | | -3=a/10-4 | | 7x-3x+18=35 | | 56=-7(-6+x) | | 5x+8y=-11 | | -22=8k-6 | | 1.2m=1.32 | | x+18/2=-19/2 | | 5/6-1/3x=1/2 | | 3(-10+a)=-51 | | 4w=182 | | 7x+7=7(x+6)-6 | | -5-7v=121 | | 8(x+3)+4(12+x)=360 | | 0-8c+1=-3 | | -5-7=121 | | 3.6=y+2 | | 0.48-0.2x=0.18 |